KONDISI OSEANOGRAFI FISIKA PERAIRAN BARAT SUMATERA (PULAU SIMEULUE DAN SEKITARNYA) PADA BULAN AGUSTUS 2007 PASCA TSUNAMI DESEMBER 2004 - Surinati, Dewi (UI Scholars Hub, 2009)
Physical Oceanographic Condition of the Western Waters of Sumatera (Simeulue Island Water) on August 2007 Pasca Tsunami December 2004. The physical oceanographic condition of the western waters of Sumatera was observed in August 2007 after tsunami disaster using the RV Baruna Jaya VII. The tenth CTD stations were observed for measuring the temperature and salinity. The temperature and salinity conditions after two years and seven months of the disaster have been normal as a usual condition. The temperature of 28 – 30o C gradually increased from north to south and salinity of 32.8 to 34 PSU gradually increased from the coastal area to the open Indian Ocean. The horizontal distributions and vertical profiles of measured parameters are explained in detail in this paper.